Development of SSCS-Based E-Modules (Search, Solve, Create, Share) to Practice Creative Thinking Skills of Students on Wave Materials in High School - Bily Pratama Putra (CV Media Inti Teknologi, 2022)
This study aims to describe the feasibility and characteristics of SSCS-based e-modules to train students' creative thinking skills on wave material and get readability responses from students. This research is a research and development (R&D) with a 3D model with the steps of define, design, and develop. Data collection techniques are non-test techniques that use observational data and questionnaires. Data analysis techniques are descriptive, qualitative, and quantitative methods. The subjects used in this study were physics teachers and class XII students at SMA Negeri 4, 7, and 9 Bengkulu City. The results of this study can be concluded that the SSCS-based e-module developed is included in the very feasible criteria with an average percentage of 88.70% and has the characteristics of an electronic module and is by the SSCS syntax, so it is worth testing and getting a very good response from students towards SSCS-based e-module readability with an average percentage of 81.81%.